2002
DOI: 10.1021/jf0202842
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Fluid Extraction of all-trans-Lycopene from Tomato

Abstract: A procedure is proposed for the supercritical fluid extraction of all-trans-lycopene from tomato using carbon dioxide at 40 degrees C without modifier. The present method minimizes the risk of degradation via isomerization and oxidation of health-promoting ingredients, such as lycopene. The effect of different experimental variables on the solvating power of the supercritical fluid was evaluated in terms of both the selectivity achievable in the process and the yield of the extraction of all-trans-lycopene. Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 32 publications
2
70
0
2
Order By: Relevance
“…Furthermore, extraction at such high temperatures may result in destruction of the raw sample. Yi et al (2009) reported that the raw material utilized in their study became scorched after 90 min of extraction at 100 C. As reported by Gomez-Prieto et al (2003) even though extraction temperature was maintained as low as 40 C, the presence of cis-lycopene could still be observed; the authors attributed this outcome to the ease with which lycopene undergoes trans-to cis-isomerization when exposed to light and oxygen.…”
Section: Effect Of Temperaturementioning
confidence: 77%
See 2 more Smart Citations
“…Furthermore, extraction at such high temperatures may result in destruction of the raw sample. Yi et al (2009) reported that the raw material utilized in their study became scorched after 90 min of extraction at 100 C. As reported by Gomez-Prieto et al (2003) even though extraction temperature was maintained as low as 40 C, the presence of cis-lycopene could still be observed; the authors attributed this outcome to the ease with which lycopene undergoes trans-to cis-isomerization when exposed to light and oxygen.…”
Section: Effect Of Temperaturementioning
confidence: 77%
“…All-trans-β-carotene is very unstable and can be easily isomerized into cis-isomers, when exposed to heat and light. Inversely, lycopene commonly occurs in the all-trans configuration, which is the most thermodynamically stable form Gomez-Prieto et al (2003;Nobre et al 2009). Mezzomo et al (2010) have stated that due to the thermodynamic stability of translycopene, there is clearly an interest in avoiding the isomerization of trans-lycopene into its cis-form when lycopene is obtained for subsequent incorporation into functional foods and nutraceuticals.…”
Section: Effect Of Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…SFE is compatible with supercritical fluid chromatography since both techniques can share the same mobile phase and devices, favoring the development of extraction and separation methodologies. This technique has been applied to successfully separate lycopene from other carotenoids in tomato fruits [43,[195][196][197][198][199].…”
Section: Supercritical Fluid Extractionmentioning
confidence: 99%
“…The effect of CO 2 density on extraction of all-trans-lycopene from tomatoes was studied and a greater yield was found at the highest density (0.90 g/mL) [198].…”
Section: Supercritical Fluid Extractionmentioning
confidence: 99%